Modern landscaping and medicinal plant loss as a legacy of colonialism in Nigeria (Lokoja as case study). (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
This paper aims to trace the history of colonial urban planning in Nigerian cities, its legacies of urban design and beautification of the environment. In Nigeria the town planning institutional frame works was established under the colonial rule which persisted to the post colonial period. In this sense the colonial era was a phase in which European institutions and values systems were transferred to Nigeria, one of which is the concept of environmental beautification with the use of plants. An investigation is carried out on the influence of colonial rule on landscaping and urban design. Findings show that the introduction of deliberate landscaping to city planning have over the years systematically led to loss of valuable indigenous plants partly due to the introduction of exotic plants. These are plants that initially were seen as sources of cure for several ailments. There is therefore the need for a rethink as to the type of plants to be used for landscaping.